THE EFFECT OF PERSONALIZED ARTIFICIAL INTELLIGENCE INTERACTION QUALITY ON IMPULSIVE STREAMING INTENTIONS MEDIATED BY AFFECTIVE RESPONSES - Armmawadin, Irsyad Daffa; Dhenabayu, Riska (Universitas Putera Batam, 2025)
This study aims to analyse the effect of artificial intelligence-based interaction quality and personalisation on impulsive purchase intention in social commerce live streaming, with affective aspects as mediating variables. A quantitative approach was used through Partial Least Squares–Structural Equation Modelling (PLS-SEM) analysis involving 105 respondents who were students at Surabaya State University. The results show that the quality of interaction and artificial intelligence-based personalisation have a positive effect on the affective aspect, which in turn increases impulsive buying intention. Both independent variables also have a direct positive effect on impulsive buying intention, while the affective aspect acts as a mediator that strengthens this relationship. This study has limitations in its focus on the TikTok platform and student respondents, so further research is recommended to expand the research object and population coverage. A total of five hypotheses were tested in this study, and all were accepted based on the PLS-SEM analysis results.